Income Inequality and Macroeconomic Imbalances under EMU - Benedicta Marzinotto (London School of Economics and Political Science (LSE), European Institute, 2016)
This paper explains the build-up and reversal of euro area macroeconomic imbalances by considering the interaction between the underlying income distribution in each country and EMU-induced financial liberalization. The argument is that the sharp increase in money supply since the early 1990s had the effect of relaxing collateral constraints for illiquid lower- income groups, whilst having no specific impact on other households. The former started over-borrowing against optimistic expectations about their future income. It follows that unequal countries such as Greece, Ireland, Italy, Portugal and Spain - where the share of lower-income groups is relatively high - had greater private debt burdens and worse external positions than equal countries. Consequently, current account reversal was asymmetric because the crisis forced these indebted households to abruptly reduce consumption not least because they were the first to be pulled out of the labour market and hardly had financial buffers. The hypothesis is tested using a difference-in-difference approach to panel data.
Keywords: F32; F41; E2; 330; current account; income inequality; financial liberalization; debt leverage; difference-in-difference